Teachers’ Clinical Supervisory Experiences with Regional Pedagogic Inspectors (RPIs) and Their Effects on the Quality of Instruction in Wouri Division of the Littoral Region of Cameroon - Alama, Nkwomen Moses (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Clinical supervision of teachers in this context involves the face to face overseeing of the teaching or instruction of teachers (supervisees) by Regional Pedagogic Inspectors (supervisors). The clinical supervision process involves three main stages: the pre-observation conference between the supervisor and supervisee; the actual classroom observation during which the supervisor observes the teaching or lesson delivery of the teacher and the post-observation conference between the supervisor and teacher. This study had three specific objectives: 1) To investigate teachers' experiences during pre-observation conferences with RPIs and their effects on the quality of teaching. 2) To investigate teachers' experiences during classroom observation by RPIs and their effects on the quality of teaching. 3) To investigate teachers' experiences during post-observation conferences with RPIs and their effects on the quality of teaching. These objectives were coined into research questions and hypotheses. The study employed a descriptive survey research design. A sample of two hundred teachers (who had experiences clinical supervision by RPIs) was selected for this study. The study used a questionnaire for teachers as the instrument to collect salient data. The findings of this study revealed that: teachers had a negative experience with RPIs because they did not carry out the pre-observation and post-observation conferences as required by the norms of clinical supervision. These experiences had a negative effect on the quality of teachers’ instruction. However, the teachers had a positive experience with RPIs during their classroom observation stage and this had a positive mark on the quality of teachers’ instruction. It was recommended that more experienced and competent teachers should be appointed as RPIs to clinically supervise teachers regularly, while carrying out all the three main stages of clinical supervision as required.